The effects of ceiling display and natural sounds on stress and anxiety among cardiac patients: A randomized controlled trial - Roghayeh Lalezari; Roghayeh Mehdipour-Rabori; Tania Dehesh; Esmat Nouhi (Kashan University of Medical Sciences, 2022)
Background: Cardiovascular disease is the most common chronic disease and the leading cause of death in the world. Stress and anxiety are among the most important risk factors of cardiovascular disease. Objectives: The aim of this study was to assess the effects of ceiling display and natural sounds on stress and anxiety among cardiac patients. Methods: This randomized controlled trial was conducted in 2018-2019 in the coronary care units (CCUs) of two teaching hospitals affiliated to Kerman University of Medical Sciences, Kerman, Iran. Participants were 220 cardiac patients randomly allocated through block randomization to four 55-person groups, namely ceiling display group, natural sounds group, combined ceiling display and natural sounds (display sound) group, and control group. The Spielberger State-Trait Anxiety Inventory and the Perceived Stress Scale were used for data collection at the beginning of the study and at the time of discharge from CCU. Data were analyzed by the Chi-square and paired-sample t-tests and the analysis of variance. Results: The mean scores of state and trait anxiety and stress significantly decreased in all intervention groups (P < 0.05) and did not significantly change in the control group (P > 0.05). There were significant differences among the groups respecting the posttest mean scores of state and trait anxiety and stress (P < 0.05). The posttest mean scores of state and trait anxiety in the combined display-sound group and the posttest mean scores of stress in the natural sounds group were significantly less than other groups. Conclusion: Ceiling display and natural sounds are effective in significantly reducing state and trait anxiety and stress among cardiac patients in CCU and their combination produces more significant effects.